2020
DOI: 10.1177/2050640620936810
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound‐based multimodal evaluation of the pancreas in patients with suspected early chronic pancreatitis

Abstract: Background Diagnosis of early chronic pancreatitis is a clinical challenge and hindered by the lack of a gold standard. Endoscopic ultrasound (EUS) and the endoscopic pancreatic function test (ePFT) are the most sensitive morphological and functional methods in this setting. EUS-elastography allows for the quantification (strain ratio) of pancreatic fibrosis, and the dynamic evaluation of the main pancreatic duct compliance provides additional information. We developed a multimodal EUS-based approach for the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…Indeed, there is ongoing debate regarding the most accurate elastographic technique. In the present study by Dominguez-Munoz and colleagues 4 it was the SR technique that gives a 'relative' stiffness measure. In SR the strain of a region of interest (ROI) is compared with the strain of a region in normal surrounding reference tissue.…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…Indeed, there is ongoing debate regarding the most accurate elastographic technique. In the present study by Dominguez-Munoz and colleagues 4 it was the SR technique that gives a 'relative' stiffness measure. In SR the strain of a region of interest (ROI) is compared with the strain of a region in normal surrounding reference tissue.…”
mentioning
confidence: 78%
“…9 EUS-EG is undoubtedly a technique that can really help to reach a diagnosis of CO and, most of all, ECP. To date few papers have been published on the diagnostic capacity of SR (fundamentally used in Spain 4 and Japan) 10 or SH. In the future comparative prospective studies about these two techniques could suggest which one should be used in the diagnosis of CP, especially ECP.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A prospective study using EUS to diagnose alcoholic early chronic pancreatitis was published in 2002 [ 13 ]. In the past two decades, early chronic pancreatitis has mostly been diagnosed by EUS in studies [ 14 , 15 , 21 , 40 , 41 , 42 , 43 , 44 , 45 ]. By definition, early chronic pancreatitis is a syndrome requiring symptoms, risk factors, biomarkers, and image diagnosis, according to an international consensus [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…EUS findings such as hyperechoic foci and strands, parenchymal lobularity, and a hyperechoic ductal wall are considered to be signs of pancreatic fibrosis[ 51 ]. A study conducted in 2016 using a quantitative receiver operating characteristic (ROC) curve analysis to evaluate the accuracy of EUS features revealed that four or more standard EUS features achieved the best balance of sensitivity (61%; 95%CI: 46.8-73.5) and specificity (75%; 95%CI: 42.8-94.2) (AUC = 0.68) for predicting abnormal pancreatic histopathology alterations of non-calcific pancreatitis.…”
Section: Imaging Modalitiesmentioning
confidence: 99%